(untitled) (SAARC Journal of Agriculture, 2022)
Insect pests are one of the most concerned biotic obstacles in agriculture and humans are constantly in search of new strategies to control them. Chemical pesticides are extensively used for controlling insect pests which cause a lot of problem, such as pest resistance, elimination of natural enemies, environmental pollution, loss of biodiversity and human health hazards. As an alternative pest control strategy, the application of nanotechnology in insect pest management can be one of the most promising ways to overcome the problems related to the application of conventional chemical pesticide. According to various research findings, the nano based materials are described as very effective in insect pest management because they have larger surface area which ensures the contact of more volume of pesticides with the insect pests. They also provide selective, targeted and long term-controlled release of formulation of nanomaterial which is ecologically more viable. Moreover, the required amount of nano-insecticide is also very small for controlling insect and thus the pesticide load in the environment gets reduced. So, use of nanotechnology for insect pest management is considered as environmentally sustainable and a brilliant insect control strategy in green agriculture. SAARC J. Agric., 19(2): 1-11 (2021)